Application of RSA-CRT Cryptographic Methods and LSB-LCG Steganography Method in Message Security Systems with Video Media - Mhd Furqan; diana vita; Sriani Sriani (INFOKUM, 2022)
This assessment was driven by joining cryptography and steganography for receiving secret messages. Cryptography is used to scramble confined data or messages, then, at that point, the Steganography cycle is finished by covering messages that have been encoded into video media so confidential data or messages are more guaranteed. RSA is the procedure picked in this audit, RSA is one of the public key estimations whose strength lies in the surprising cycle and taking into account numbers into two resolute numbers and RSA-CRT is set to augment working time capability got together with the Steganography system, where messages are implanted into parts of 7 on the pixel data that shapes the image record sequentially. The usage of a mix of the two procedures can fabricate the security of the message to be installed and delivered off the recipient of the secret message. This study plans to grow the security of the text by inserting text into the video, then, scramble the text so the text ought not be apparent.